Molded body
Patent Information
- Application Number
- JP2021075595
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-28
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-04-28
AI Technical Summary
【0006】 本開示の成形体は、金属部材と接触するように用いても、金属部材の電食劣化が抑制され、しかも成形性が良好である。
Smart Images

Figure 0007636258000002 
Figure 0007636258000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a molded body. [Background technology]
[0002] The molded article, which is a vulcanizate of the rubber composition, may be used in contact with a metal member. For example, when the molded article is a hose, it is used so as to be in contact with a metal clamp for fixing. If the molded article is in contact with the metal member, electricity may flow to the metal member through the molded article, causing the metal member to deteriorate due to electrolytic corrosion. Therefore, in order to suppress the electrolytic deterioration of metal members, techniques for improving the volume resistivity of molded bodies have been studied. For example, Patent Document 1 studies a technique of blending clay, which is an insulating filler. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-72291 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, when the amount of clay is increased, the amount of carbon black used as a reinforcing material must be reduced, which may result in a decrease in moldability. The present disclosure has been made in consideration of the above-mentioned circumstances, and aims to provide a molded body that suppresses electrolytic deterioration of metal members even when used in contact with the metal members, and also has good formability. The present disclosure can be realized in the following forms. [Means for solving the problem]
[0005] A molded article which is a vulcanizate of a rubber composition, The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 6 A compact having a resistivity of Ω·cm or more. Effect of the Invention
[0006] Even when the molded article of the present disclosure is used in contact with a metal member, the deterioration of the metal member due to electrolytic corrosion is suppressed and the moldability is good. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a perspective view showing an example of a molded body 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Here, a preferred example of the present disclosure is given. [2] A molded body, wherein the hardness of the vulcanizate is 70 or more and 90 or less. [3] A molded article, wherein the rubber composition contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber. [4] The ethylene-α-olefin-non-conjugated polyene copolymer rubber is Contains ethylene units, α-olefin units, and non-conjugated polyene units; a molded article having an ethylene unit content of 60% by mass or more and 90% by mass or less, where the total of the ethylene unit content, the α-olefin unit content, and the non-conjugated polyene unit content is 100% by mass. [5] The rubber composition contains an inorganic filler, The molded article, wherein the content of the inorganic filler in the rubber composition is 15.0% by mass or more and 40.0% by mass or less. [6] The rubber composition contains carbon black, The molded article, wherein the content of the carbon black in the rubber composition is 20.0% by mass or more and 45.0% by mass or less. [7] A molded product, wherein a ratio of the carbon black to the inorganic filler (the carbon black / the inorganic filler) is 0.70 or more and 1.40 or less in mass ratio. [8] A molded body having a hose shape.
[0009] The present disclosure will be described in detail below. In this specification, a description using "~" for a numerical range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".
[0010] 1. Molded body 1 The molded article 1 is a vulcanizate of a rubber composition. The 50% modulus of the vulcanizate of the molded article 1 is 2.7 MPa or more. The volume resistivity of the vulcanizate of the molded article is 1×10 6 The resistance of the molded body 1 is Ω·cm or more. An example of the molded body 1 is shown in FIG. 1. The shape of the molded body 1 is not particularly limited. The molded body 1 in FIG. 1 has a hose shape. This molded body 1 is an example of an air cleaner hose. An air cleaner hose is generally installed in an engine room and has a function of guiding clean air that has passed through an air cleaner to the engine.
[0011] (1) Rubber composition (1.1) Rubber The rubber composition contains a rubber (polymer). The type of rubber is not particularly limited. Suitable examples of the rubber include ethylene-α-olefin-non-conjugated polyene copolymer rubber, acrylonitrile butadiene copolymer, and chloroprene rubber. These rubbers may be used alone or in combination of two or more.
[0012] The rubber composition preferably contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber as the rubber. The α-olefin of the ethylene-α-olefin-non-conjugated polyene copolymer rubber is not particularly limited. Suitable examples of the α-olefin include α-olefins having 3 to 20 carbon atoms. Specific examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-octene, 1-nonene, 1-decene, and 1-undecene. These α-olefins may be used alone or in combination of two or more. As the α-olefin, propylene, 1-butene, 1-hexene, and 1-octene are preferred, and propylene is particularly preferred. The non-conjugated polyene used in the ethylene-α-olefin-non-conjugated polyene copolymer rubber is not particularly limited. Suitable examples of the non-conjugated polyene include non-conjugated polyenes having 3 to 20 carbon atoms. Specific examples of the non-conjugated polyene include 1,4-hexadiene, dicyclopentadiene, and 5-ethylidene-2-norbornene. These non-conjugated polyenes may be used alone or in combination of two or more.
[0013] The ethylene-α-olefin-non-conjugated polyene copolymer rubber contains ethylene units, α-olefin units, and non-conjugated polyene units. "Ethylene units" means monomer units derived from ethylene. "α-olefin units" means monomer units derived from α-olefins. "Non-conjugated polyene units" means monomer units derived from non-conjugated polyenes. The content of the ethylene unit in the ethylene-α-olefin-non-conjugated polyene copolymer rubber is not particularly limited. The content of the ethylene unit may be contained from the viewpoint of good moldability of the rubber composition, and when the total of the content of the ethylene unit, the content of the α-olefin unit, and the content of the non-conjugated polyene unit is taken as 100 mass%, it is greater than 0 mass%, preferably 60 mass% or more, more preferably 63 mass% or more, and even more preferably 68 mass% or more. On the other hand, the content of the ethylene unit is preferably 90 mass% or less, more preferably 85 mass% or less, and even more preferably 80 mass% or less. From these viewpoints, the content of the ethylene unit is preferably 60 mass% or more and 90 mass% or less, more preferably 63 mass% or more and 85 mass% or less, and even more preferably 68 mass% or more and 80 mass% or less. It is preferable that the above-mentioned content of the ethylene unit is contained. When multiple types of ethylene-α-olefin-non-conjugated polyene copolymer rubbers having different ethylene unit contents are used, it is preferable that the ethylene unit content of at least one type of ethylene-α-olefin-non-conjugated polyene copolymer rubber is within the above range. The ethylene unit content is determined by the FTIR method according to ASTM D3900.
[0014] The content of the non-conjugated polyene unit in the ethylene-α-olefin-non-conjugated polyene copolymer rubber is not particularly limited. The content of the non-conjugated polyene unit is preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 4% by mass or more, when the total of the content of the ethylene unit, the content of the α-olefin unit, and the content of the non-conjugated polyene unit is 100% by mass. On the other hand, the content of the non-conjugated polyene unit is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. From these viewpoints, the content of the non-conjugated polyene unit is preferably 2% by mass or more and 15% by mass or less, more preferably 3% by mass or more and 10% by mass or less, and even more preferably 4% by mass or more and 5% by mass or less. When multiple types of ethylene-α-olefin-non-conjugated polyene copolymer rubbers having different contents of non-conjugated polyene units are used, it is preferable that the content of non-conjugated polyene units in at least one type of ethylene-α-olefin-non-conjugated polyene copolymer rubber is within the above range. The content of non-conjugated polyene units is determined by the FTIR method according to ASTM D6047.
[0015] (1.2) Fillers (1.2.1) Inorganic fillers The rubber composition preferably contains an inorganic filler (excluding carbon black). When the rubber composition contains an inorganic filler, the volume resistivity of the molded article is improved, and deterioration due to electrolytic corrosion of metal members can be suppressed. The inorganic filler is not particularly limited. Examples of the inorganic filler include calcium carbonate, magnesium carbonate, aluminum hydroxide, calcium silicate, clay, talc, and silica. The inorganic filler may be used alone or in combination of two or more. The inorganic filler may also be called a white filler. The content of the inorganic filler is not particularly limited. From the viewpoint of improving the volume resistivity of the molded body, the content of the inorganic filler in the rubber composition is preferably 15.0 mass% or more, more preferably 20.0 mass% or more, and even more preferably 25.0 mass% or more, when the rubber composition is 100 mass%. On the other hand, from the viewpoint of improving the moldability of the rubber composition, the inorganic filler is preferably 40.0 mass% or less, more preferably 35.0 mass% or less, and even more preferably 30.0 mass% or less. From these viewpoints, the content of the inorganic filler is preferably 15.0 mass% or more and 40.0 mass% or less, more preferably 20.0 mass% or more and 35.0 mass% or less, and even more preferably 25.0 mass% or more and 30.0 mass% or less.
[0016] (1.2.2) Carbon black From the viewpoint of moldability of the rubber composition, it is preferable that the rubber composition contains carbon black. The type of carbon black is not particularly limited. Examples of carbon black include HAF (High Abrasion Furnace), SAF (Super Abrasion Furnace), ISAF (Intermediate SAF), ISAF-HM (Intermediate SAF-High Modulus), FEF (Fast Extrusion Furnace), MAF (Medium Abrasion Furnace), GPF (General Purpose Furnace), and SRF (Semi-Reinforcing Furnace). Only one type of carbon black may be used, or two or more types may be used in combination. The iodine adsorption amount (IA) of carbon black is not particularly limited. IA is a value measured in accordance with JIS K6217-1:2008. When multiple types of carbon black are used, the IA is a value measured on a mixture of multiple types of carbon black as a sample. The iodine adsorption amount of carbon black is preferably 10 to 160 mg / g, more preferably 15 to 100 mg / g, and even more preferably 20 to 50 mg / g. The content of carbon black is not particularly limited. From the viewpoint of improving moldability even in a thin-walled article, the content of carbon black in the rubber composition is preferably 20.0 mass% or more, more preferably 24.0 mass% or more, and even more preferably 28.0 mass% or more, when the rubber composition is taken as 100 mass%. On the other hand, from the viewpoint of suppressing electrolytic corrosion deterioration of metal members, the carbon black content is preferably 45.0 mass% or less, more preferably 40.0 mass% or less, and even more preferably 35.0 mass% or less. From these viewpoints, the content of carbon black is preferably 20.0 mass% or more and 45.0 mass% or less, more preferably 24.0 mass% or more and 40.0 mass% or less, and even more preferably 28.0 mass% or more and 35.0 mass% or less.
[0017] (1.2.3) Ratio of carbon black to inorganic filler The ratio of carbon black to the inorganic filler is not particularly limited. The ratio of carbon black to inorganic filler (carbon black / inorganic filler) is preferably 0.70 to 1.50 in mass ratio, more preferably 0.90 to 1.40, and even more preferably 1.00 to 1.30. Within this range, even if the molded article is used in contact with a metal member, the metal member is prevented from being deteriorated by electrolytic corrosion, and the moldability of the rubber composition is good.
[0018] (1.2.4) Total amount of inorganic fillers and carbon black The total amount of the inorganic filler (excluding carbon black) and the carbon black is not particularly limited, and is preferably 150 parts by mass or more and 300 parts by mass or less, and more preferably 180 parts by mass or more and 250 parts by mass or less, based on 100 parts by mass of the rubber.
[0019] (1.3) Other ingredients In addition to the rubber and the filler, the rubber composition may contain, as necessary, a softener, a vulcanizing agent, a vulcanization accelerator, a crosslinking aid, etc. These may be used alone or in combination of two or more kinds.
[0020] (1.3.1) Softeners The softener is not particularly limited. Examples of the softener include fatty acids such as stearic acid and their esters, fatty acid metal salts such as zinc stearate and calcium stearate, glycols such as polyethylene glycol, process oils, lubricating oils, paraffin, petroleum asphalt, castor oil, factice, etc. The softener may be used alone or in combination of two or more kinds. The content of the softener is not particularly limited. From the viewpoint of ensuring the hardness of the vulcanizate while maintaining the processability, the content of the softener is preferably 20 parts by mass or more and 120 parts by mass or less, based on 100 parts by mass of the rubber.
[0021] (1.3.2) Vulcanizing agents As the vulcanizing agent, for example, sulfur, organic peroxide (peroxide vulcanizing agent), etc. are suitably used. The softening agents may be used alone or in combination of two or more kinds.
[0022] (1.3.2.1) Sulfur The sulfur is not particularly limited, and examples of the sulfur that can be suitably used include powdered sulfur, precipitated sulfur, colloidal sulfur, and insoluble sulfur. The amount of sulfur is not particularly limited, but is preferably 0.3 parts by mass or more and 5.0 parts by mass or less, based on 100 parts by mass of rubber, from the viewpoint of allowing vulcanization to proceed appropriately and suppressing the occurrence of bloom after vulcanization.
[0023] (1.3.2.2)Organic peroxides The organic peroxide is not particularly limited. Examples of the organic peroxide include dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-(t-butylperoxy)hexyne-3, di-t-butyl peroxide, di-t-butylperoxide-3,3,5-trimethylcyclohexane, and 1,3-bis(t-butylperoxyisopropyl)benzene. The organic peroxide may be used alone or in combination of two or more kinds.
[0024] (1.3.2.3) Crosslinked form Suitable examples of the crosslinking form include sulfur-based crosslinking, resin-based crosslinking, organic peroxide-based crosslinking, etc. The crosslinking forms may be used alone or in combination of two or more.
[0025] (1.3.3) Vulcanization accelerators Examples of the vulcanization accelerator when sulfur is used include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, dipentamethylenethiuram monosulfide, dipentamethylenethiuram disulfide, dipentamethylenethiuram tetrasulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, N,N'-dioctadecyl-N,N'-diisopropylthiuram disulfide, N-cyclohexyl-2-benzothiazolylsulfenamide, N-oxydiethylene-2-benzothiazolylsulfenamide, N,N-diisopropyl-2-benzothiazolylsulfenamide, 2-mercaptobenzothiazole, 2-(2,4- Dinitrophenyl)mercaptobenzothiazole, 2-(2,6-diethyl-4-morpholinothio)benzothiazole, dibenzothiazyl disulfide, diphenylguanidine, triphenylguanidine, acetaldehyde-aniline reactant, butylaldehyde-aniline condensate, hexamethylenetetramine, acetaldehyde ammonia, 2-mercaptoimidazoline, diethylthiourea, dibutylthiourea, trimethylthiourea, di-o-tolylthiourea, zinc dimethyldithiocarbamate, zinc diethylthiocarbamate, zinc di-n-butyldithiocarbamate, zinc ethylphenyldithiocarbamate, zinc butylphenyldithiocarbamate, tellurium diethyldithiocarbamate, zinc dibutylxanthate, etc. The vulcanization accelerator may be used alone or in combination of two or more kinds. It is preferable to use two or more kinds of vulcanization accelerators in combination. The amount of the vulcanization accelerator is preferably determined to be an optimum amount depending on the required physical properties. The amount of the vulcanization accelerator is preferably 2 parts by mass or more and 8 parts by mass or less, based on 100 parts by mass of rubber, from the viewpoint of appropriately progressing the vulcanization and suppressing the occurrence of bloom after vulcanization.
[0026] (1.3.4) Crosslinking coagent Examples of crosslinking aids when using organic peroxides include p,p'-dibenzoylquinone dioxime, triallyl isocyanurate, N,N'-m-phenylene bismaleimide, methyl methacrylate, ethyl methacrylate, propyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, methacryloxyethyl phosphate, 1,4-butanediol diacrylate, ethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, neopentyl glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, trimethylolethane trimethacrylate, trimethylolpropane trimethacrylate, allyl glycidyl ether, N-methylol methacrylamide, zinc methacrylate, calcium methacrylate, magnesium methacrylate, etc. The crosslinking aids may be used alone or in combination of two or more.
[0027] (1.3.5) Paraffinic processing oil The rubber composition may contain a paraffinic processing oil. The paraffin-based process oil may be a commercially available product, such as Diana Process Oil "PS-430", "PS-32", "PS-90", "PW-32", "PW-90", "PW-150", or "PW-380" manufactured by Idemitsu Kosan Co., Ltd. The amount of the paraffin-based process oil is not particularly limited, but is preferably 10 parts by mass or more and 50 parts by mass or less, and more preferably 20 parts by mass or more and 40 parts by mass or less, based on 100 parts by mass of the rubber.
[0028] (1.3.6) Other ingredients than those mentioned above The rubber composition may also contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, flame retardants, pigments, and foaming agents, if necessary.
[0029] (1.4) Mooney viscosity of rubber composition (uncrosslinked rubber) From the viewpoint of moldability, the Mooney viscosity [ML(1+4)125°C] of the uncrosslinked rubber composition is preferably 60 or less. The Mooney viscosity [ML(1+4)125°C] of the uncrosslinked rubber composition is usually 50 or more. The Mooney viscosity (ML(1+4)125°C) is measured in accordance with JIS K6300 using a Mooney viscometer (SMV 300 model, manufactured by Shimadzu Corporation) at 125°C. In this case, the ML(1+4)125°C is obtained 5 minutes after the start of the measurement.
[0030] (2) Characteristics of the vulcanized rubber composition (2.1) 50% Modulus The 50% modulus of the vulcanizate is 2.7 MPa or more, preferably 2.8 MPa or more, and more preferably 2.9 MPa or more, from the viewpoint of ensuring sufficient strength of articles having a thin-walled shape, etc. The 50% modulus of the vulcanizate is usually 5 MPa or less. The method for measuring the 50% modulus is as follows: A No. 3 dumbbell test piece as specified in JIS K6251 is prepared by punching out a vulcanized rubber sheet. Using this test piece and a tensile tester (Shimadzu Corporation AGS-1kNX), the 50% modulus (M50) is measured according to the method specified in JIS K6251 at a measurement temperature of 25°C and a tensile speed of 500 mm / min.
[0031] (2.2) Volume resistivity The volume resistivity of the vulcanizate is set to 1×10 6 Ω cm or more, 1×10 7 Ω·cm or more is preferable, and 1×10 8 More preferably, it is Ω·cm or more. The volume resistivity of the vulcanizate is usually 1×10 11 Ω·cm or less. The volume resistivity is measured according to JIS K6271 by sandwiching a sample (vulcanized rubber sheet) between metal electrodes using a 2mm x 100mm x 100mm vulcanized rubber sheet (sheet of vulcanized material) with a smooth surface and an ammeter (Advantest Electrometer R8340) at 25℃ and 1V.
[0032] (2.3)Hardness The hardness of the vulcanizate is preferably 70 or more and 90 or less, more preferably 75 or more and 85 or less, and even more preferably 77 or more and 83 or less, from the viewpoint of application to thin-walled articles. If the hardness is in this range, for example, even if it is in the form of a hose, it can withstand pressure changes such as negative pressure, and is therefore suitable for air cleaner hoses and the like. Hardness (A hardness) is measured in accordance with JIS K6253. That is, the hardness of a sheet (Type A durometer, HA) is measured using three 2 mm vulcanized rubber sheets (vulcanized product sheets) with smooth surfaces, with the flat parts stacked to a thickness of approximately 6 mm.
[0033] 2. Manufacturing method of molded body 1 The method for producing the molded body 1 is not particularly limited. The molded body 1 is produced, for example, as follows. (1) Preparation of Rubber Composition A rubber compound is prepared by compounding rubber (polymer) with a given amount of filler, softener, etc. The rubber compound is then kneaded with a twin-screw kneader such as a mixer, and a vulcanizing agent and a vulcanization accelerator are added to prepare a rubber composition. (2) Preparation of Molded Body 1 The rubber composition is molded into a predetermined shape and then vulcanized at a predetermined temperature to produce the molded article 1. When the molded article 1 has a hose shape, there is no particular limitation on the thickness. In the case of a hose shape, the maximum thickness of the molded article 1 can be, for example, 2.0 mm or more and 5.0 mm or less. EXAMPLES
[0034] The present invention will be described more specifically below with reference to examples.
[0035] 1. Preparation of Molded Articles (Examples 1-4 and Comparative Examples 1-2) Various molded bodies were produced using the blending ratios shown in Table 1-3. Details of the main raw materials in Table 1 are shown below.
[0036] [Table 1]
[0037] (1) Main raw materials (1.1) Ethylene-α-olefin-non-conjugated polyene copolymer rubber The following polymers were used as ethylene-α-olefin-non-conjugated polyene copolymer rubbers. Note that since polymer C contains a polymer component and an oil component, the amounts of both (polymer component, oil component) are listed separately in Table 1. Polymer A: EPDM Keltan 2650 LANXESS Non-conjugated polyene unit content 6% by mass, ethylene unit content 53% by mass Polymer B: EPDM EPT3092M manufactured by Mitsui Chemicals, Inc. Non-conjugated polyene unit content 5% by mass, ethylene unit content 65% by mass Polymer C: EPDM Esprene 600F manufactured by Sumitomo Chemical Co., Ltd. Non-conjugated polyene unit content 4% by mass, ethylene unit content 66% by mass Oil content of Polymer C: Paraffin oil Polymer C contains 50% by mass of polymer and 50% by mass of oil. Polymer D: EPDM NORDEL IP4725P Dow Chemical Non-conjugated polyene unit content 5% by mass, ethylene unit content 70% by mass Polymer E: EPDM K9720 manufactured by Mitsui Chemicals, Inc. Non-conjugated polyene unit content 10% by mass, ethylene unit content 77% by mass
[0038] (1.2) Carbon black Carbon black FEF: Asahi #60UG (FEF) manufactured by Asahi Carbon Co., Ltd., iodine adsorption capacity IA 41mg / g Carbon black SRF: Asahi #50G (SRF) manufactured by Asahi Carbon Co., Ltd., iodine adsorption capacity IA 27mg / g (1.3) Inorganic fillers White filler: Burgess Pigment Berkes KE is a clay made primarily of aluminum silicate (SiO2: 51.7% Al2O3: 43.2%). (1.4) Paraffin-based process oil (abbreviated as "process oil" in the table) Process oil: Diana Process PS-430 manufactured by Idemitsu Kosan Co., Ltd. (1.5) Common small amount of mixture materials The following ingredients were blended in all samples: Zinc oxide type 2: 5.00 parts by weight (phr) manufactured by Hakusui Tech Co., Ltd. Stearic acid: 1.00 parts by weight (phr) manufactured by NOF Corporation PEG#4000: 2.00 parts by weight (phr) manufactured by Adeka Corporation - Hitanol 1501: 1.50 parts by weight (phr) Hitachi Chemical Co., Ltd. Struktol WB-16: 0.20 parts by weight (phr) manufactured by S&S Co., Ltd. Lenogran CBS-80 (N-cyclohexyl-2-benzothiazylsulfenamide): 2.13 parts by mass (phr) manufactured by LANXESS Lenogran ZDBC-80 (zinc dibutyldithiocarbamate): 1.25 parts by mass (phr) manufactured by LANXESS Sunmix TT-75 (thiuram vulcanization accelerator): 0.76 parts by weight (phr) Sanshin Chemical Industry Co., Ltd. Sunmix TRA-70 (thiuram vulcanization accelerator): 0.71 parts by weight (phr) Sanshin Chemical Industry Co., Ltd. Rhenogran S-80 (sulfur): 0.75 parts by weight (phr) manufactured by LANXESS Valnoc R (4,4'-dithiodimorpholine): 1.50 parts by mass (phr) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0039] The total amount (parts by mass) of carbon black means the total amount of carbon black FEF and carbon black SRF. The total amount (mass%) of carbon black is the ratio of the total amount (mass parts) of carbon black to the total amount (mass parts) of the composition. This ratio corresponds to the carbon black content (mass%) of the present disclosure. The white filler (mass%) is the ratio of the white filler (parts by mass) to the total amount (parts by mass) of the composition. This ratio corresponds to the content (mass%) of the inorganic filler of the present disclosure. The ratio (mass ratio) of carbon black / white filler corresponds to the mass ratio of carbon black / inorganic filler of the present disclosure. The total amount of filler is the combined amount of carbon black and white filler. The total amount of oil (parts by mass) is the combined total of the oil content of polymer C and the paraffin-based process oil. The total amount of oil (mass %) is the ratio of the total amount of oil (parts by mass) to the total amount (parts by mass) of the composition.
[0040] (2) Preparation of molded body Specifically, the molded body was produced as follows. A rubber compound was prepared by blending a polymer with a specified amount of carbon black, white filler, softener, etc. The compound was then mixed with a twin-screw mixer such as a mixer (discharge temperature 100°C, rotation speed 25 rpm), and a vulcanizing agent and vulcanization accelerator were added with an 8-inch roll to prepare a rubber composition. The rubber composition was molded and processed into a shape suitable for the test method, and then vulcanized at 170°C for 10 minutes to produce a vulcanized rubber molded body.
[0041] 2. Evaluation Method The Mooney viscosity of the rubber composition (uncrosslinked rubber) was measured by the method described in the section "(1) Rubber composition (1.4) Mooney viscosity of rubber composition (uncrosslinked rubber)". The 50% modulus, volume resistivity, and hardness of the vulcanizate were measured by the methods described in the section "(2) Properties of vulcanizate of rubber composition."
[0042] 3.Results The results are shown in Table 1. (1) Mooney viscosity (ML(1+4)125℃) In Table 1, the A in the Mooney viscosity column has the following meaning: A: The Mooney viscosity is 60 or less, and the moldability of the unvulcanized rubber composition is good. (2)Hardness In Table 1, A and B in the hardness column have the following meanings. A: The hardness is 70 to 90, and it can be applied to thin-walled articles. B: The hardness is less than 70, and is not suitable for thin-walled articles. (3) 50% modulus In Table 1, A and B in the 50% modulus column have the following meanings. A: The 50% modulus is 2.7 or more, and it can be applied to thin-walled articles. B: The 50% modulus is less than 2.7, and is not suitable for thin-walled articles. (4) Volume resistivity In Table 1, A and B in the volume resistivity column have the following meanings. A: Volume resistivity is 1.0×10 6 Its resistance to corrosion is Ω·cm or more, and even when used in contact with metal parts, deterioration of the metal parts due to electrolytic corrosion is suppressed. B: Volume resistivity is 1.0×10 6 Its resistance is less than Ω·cm, and if it is used in contact with metal parts, it will cause electrolytic corrosion and deterioration of the metal parts. (5) Overall Judgment In Table 1, "OK" and "NG" in the overall judgment column have the following meanings: OK: The unvulcanized rubber composition has good moldability, and the properties of the vulcanized product are also good. NG: The properties of the vulcanizate are poor.
[0043] (6) Fulfillment of each requirement in Examples 1-4 Examples 1-4 satisfy all of the following requirements (a)-(h). · Requirement (a): 50% modulus of the vulcanizate is 2.7Mpa or more. Requirement (b): The volume resistivity of the vulcanizate is 1×10 6 Ω·cm or more. · Requirement (c): The hardness of the vulcanizate is 70 to 90. Requirement (d): The rubber composition contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber. · Requirement (e): In the ethylene-α-olefin-non-conjugated polyene copolymer rubber, the content of ethylene units is 60% by mass or more and 90% by mass or less. Requirement (f): The material contains an inorganic filler, and the content of the inorganic filler is 15.0% by mass or more and 40.0% by mass or less. Requirement (g): Carbon black is contained, and the carbon black content is 20.0% by mass or more and 45.0% by mass or less. Requirement (h): The ratio of carbon black to inorganic filler (carbon black / inorganic filler) is between 0.70 and 1.40 in mass ratio.
[0044] (7) Fulfillment of each requirement in Comparative Examples 1-3 In contrast, Comparative Example 1-3 does not satisfy the following requirements. Comparative Example 1 does not satisfy the requirements (b), (f), (g), and (h). Comparative Example 2 does not satisfy the requirements (a) and (c). Comparative Example 3 does not satisfy the requirements (a) and (c).
[0045] (8) Results and Discussion Example 1-4 was judged to be good overall, that is, in Example 1-4, the moldability of the unvulcanized rubber composition was good, and the properties of the vulcanized product were also good. In contrast, in Comparative Example 1 which did not contain an inorganic filler (white filler), the volume resistivity of the vulcanizate was low and the overall evaluation was also poor. In Comparative Example 2, the 50% modulus of the vulcanized product was low, the hardness of the vulcanized product was also low, and the overall evaluation was poor. In Comparative Example 3, the 50% modulus of the vulcanized product was low, the hardness of the vulcanized product was also low, and the overall evaluation was poor. In Comparative Example 3, 50 parts by mass of EPDM (polymer A) with a low ethylene unit content of 53 mass% was used in 100 parts by mass of EPDM, and the overall evaluation was poor. Therefore, it is found that it is preferable that, in 100 parts by mass of EPDM used as a raw material, at least more than 50 parts by mass of EPDM has an ethylene unit content of 60% to 90% by mass.
[0046] 4. Effects of the embodiment Examples 1-4 suppress the electrolytic deterioration of metal members even when used in contact with the metal members, and further have good formability and are applicable to articles having thin walls.
[0047] The present disclosure is not limited to the above-described embodiments, and various modifications and variations are possible. [Explanation of symbols]
[0048] 1...Molded body
Claims
1. A molded article which is a vulcanizate of a rubber composition (excluding those containing calcium carbonate), The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 Ω cm or more, The hardness of the vulcanizate is 75 or more, The rubber composition contains clay, The molded article, wherein the content of the clay in the rubber composition is 15.0% by mass or more and 30.0% by mass or less.
2. A molded article which is a vulcanizate of a rubber composition (excluding those containing cellulose fibers, polyamide fibers or oxidized cellulose fibers), The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 Ω cm or more, The hardness of the vulcanizate is 75 or more, The rubber composition contains carbon black, The molded article, wherein the content of the carbon black in the rubber composition is 29.0 mass % or more and 45.0 mass % or less.
3. A molded article which is a vulcanizate of a rubber composition (excluding those containing cellulose fibers, polyamide fibers or oxidized cellulose fibers), The 50% modulus of the vulcanizate is 2.9 MPa or more, The volume resistivity of the vulcanizate is 1×10 Ω cm or more, The rubber composition contains carbon black, The molded article, wherein the content of the carbon black in the rubber composition is 29.0 mass % or more and 45.0 mass % or less.
4. A molded article which is a vulcanizate of a rubber composition (excluding those containing cellulose fibers, polyamide fibers or oxidized cellulose fibers), The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 6 Ω cm or more, The rubber composition contains an inorganic filler, The content of the inorganic filler in the rubber composition is 15.0 mass% or more and 40.0 mass% or less, The rubber composition contains carbon black, The molded article, wherein the content of the carbon black in the rubber composition is 31.7% by mass or more and 45.0% by mass or less.
5. A molded article which is a vulcanizate of a rubber composition, The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 6 Ω cm or more, The rubber composition contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber, The rubber composition contains an inorganic filler, The content of the inorganic filler in the rubber composition is 15.0 mass% or more and 40.0 mass% or less, The rubber composition contains carbon black, The content of the carbon black in the rubber composition is 31.7% by mass or more and 45.0% by mass or less, A molded product, wherein a ratio of the carbon black to the inorganic filler (the carbon black / the inorganic filler) is 0.70 or more and 1.40 or less in terms of mass ratio.
6. A molded article which is a vulcanizate of a rubber composition, The 50% modulus of the vulcanizate is 2.7 MPa or more, The volume resistivity of the vulcanizate is 1×10 Ω cm or more, The hardness of the vulcanizate is 75 or more, The rubber composition contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber, The rubber composition contains an inorganic filler, The content of the inorganic filler in the rubber composition is 15.0 mass% or more and 40.0 mass% or less, The rubber composition contains carbon black, The content of the carbon black in the rubber composition is 29.0 mass% or more and 45.0 mass% or less, A molded product, wherein a ratio of the carbon black to the inorganic filler (the carbon black / the inorganic filler) is 0.70 or more and 1.40 or less in terms of mass ratio.
7. A molded article which is a vulcanizate of a rubber composition, The 50% modulus of the vulcanizate is 2.9 MPa or more, The volume resistivity of the vulcanizate is 1×10 Ω cm or more, The rubber composition contains an ethylene-α-olefin-non-conjugated polyene copolymer rubber, The rubber composition contains an inorganic filler, The content of the inorganic filler in the rubber composition is 15.0 mass% or more and 40.0 mass% or less, The rubber composition contains carbon black, The content of the carbon black in the rubber composition is 29.0 mass% or more and 45.0 mass% or less, A molded product, wherein a ratio of the carbon black to the inorganic filler (the carbon black / the inorganic filler) is 0.70 or more and 1.40 or less in terms of mass ratio.
8. The molded article according to claim 1 , which has a hose shape.
Citation Information
Patent Citations
Insulation covering material having improved physical properties
JP1990109204A
Radiator hose
JP1997025374A
Connecting structure for aqueous medium transport hose
JP1999315965A
Rubber composition for water hose, and water hose obtained by using the same
JP2012072291A
Flame retardant composition
JP2013194232A